The Main Trends And Directions Of Cultural And Humanitarian Cooperation Between China And Kazakhstan Within The Belt And Road Initiative - Baisultanova, Kulipa; Duisekina, Aidana; Dauletova, Gauhar; Ustemirova, Aigerim; Ashinova, Zhanar (Opción, 2019)
The main historical aspects of cooperation between the Republic of Kazakh- stan and the People’s Republic of China in the social, humanitarian and cul- tural spheres are considered in the article, the main regulatory documents, both in historical retrospective and in the context of the implementation of the Belt and road initiative (BRI) are identified and summarized. The authors believe that in the modern period, the cultural and humanitar- ian cooperation between the two countries within the international project “Silk Road Economic Belt” (SREB) is acquiring new trends. In the rapidly changing international situation, the growing factors of instability and unpre- dictability, cultural and humanitarian cooperation can not only revive trade relations along the Silk Road, but also contribute to the maintaining of peace and stability at the regional level. The authors also noted that the cultural and humanitarian aspect of the SREB for various reasons in Kazakhstan society can be perceived as a tool of “soft power” of China.